Using Social Media Online for Communication in Organization and Work Engagement Predicting Job Performance of Personnel in Districts of Bangkok Metropolitan - สุวิสุทธิ์, ชุลีวรรณ; ศักดิ์ศรี, สุนทรี (Ratchaphruek Journal, 2018)
ABSTRACT The objectives of this research were 1) to study the level of job performance of personnel in districts of Bangkok Metropolitan, 2) to study relationships between using social media online for communication in organization and job performance of personnel, 3) to study relationships between work engagement and job performance of personnel, and 4) to predict job performance of personnel with using social media online for communication in organization and work engagement. The samples were 313 personnel in districts of Bangkok Metropolitan. The research instrument was a questionnaire. The statistics for data analysis were percentage, mean, standard deviation, Pearson Product Moment Correlation Coefficient and Stepwise Multiple. The results revealed that 1) job performance of personnel was in high level, using social media online for communication in organization and work engagement were in high level, 2) there was a positive relationship between using social media online for communication in organization and job performance of personnel, and between work engagement and job performance of personnel with a statistical significance at .01 level, and 3) work engagement in two facets of dedication and absorption, in cross-channel communication and downward communication accounted for 45.40% of the variance in job performance of personnel.